The Function of Parents in Rundeng Village's West Aceh District Character Education Program for Children - Cintia Amelia Pratiwi; Rahmat Saputra (PGMI IAIN Lhokseumawe, 2023)
This study aims to determine the role of parents in children's character education and to find out the obstacles in children's character education in Rundeng Village, West Aceh District. This research is qualitative descriptive research with data collection techniques using observation and interviews. The results of the study show that parents have played a role in building children's character by teaching honesty, mutual respect, courtesy, kindness, friendliness, and obeying rules so that children have good character. The obstacles faced by parents in character education for children in Rundeng Village, District West Aceh, namely environmental and time factors in educating children to have good character.